In-School CSR and its impact on brand image, brand identification and brand reputation: the moderator effect of brand familiarity, product involvement and cause-brand fit - Carrilha, Nina Sampaio (2014)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics